ANALISIS SISTEM APPRAISAL BERITA PROSES EKSEKUSI DUO BALI NINE (PENDEKATAN LINGUISTIK SISTEMIK FUNGSIONAL) - Pusparini, Ayu; Djatmika, Djatmika; Santosa, Riyadi (Universitas Negeri Surabaya, 2017)
This research explores the appraisal system in the news texts exposing issue of Duo Bali Nine execution taken from The Sydney Morning Herald, The Guardian Australia, The Jakarta Globe and The Jakarta Post websites. This is a descriptive qualitative research using criterion-based sampling technique. The primary data are taken from the interview and from the sixteen analyzed texts.the secondary data are taken from all information about journalists and the news paper also all information about Duo Bali Nine execution. The objectives of the research are to find out the appraisal systems applied in those texts, to know the journalists? position through their texts and the influences of appraisal systems toward the readers. The results show that each news paper has their own appraisal systems patern. All types of attitudes are applied in the news texts both positive and negative. The engagement is mostly heterogloss and the mostly graduation is force- raise. Heterogloss engagement to make as if jurnalist in the neutral position and force raise graduation to make the effective news and reader not easily forget about the news.